Utilization Of Fermented Tofu Waste As Additional Feed On The Growth Of Tilapia (Oreochromis Niloticus) - Melisa Dwi Rizki; Retno Cahya Mukti (Barakuda'45, 2022)
The high cost of commercial feed is a problem that many fish farmers face which results in lower profits. Therefore, it needs additional feed others with a relatively cheap price, but do not inhibit the growth of fish to harvest. Tofu waste which has crude protein of 21.66% so that it can meet the nutritional needs of fish, but tofu waste also has crude fiber of 20.26% so that tofu waste needs to be fermented with probiotics because probiotics can break down undigested components and increase digestibility so that the use of feed become more efficient and growth becomes more optimal. The purpose of this study was to determine the effect of tofu waste fermented with probiotics as additional feed to increase growth in tilapia (Oreochromis niloticus). This research was conducted in September – October 2020. This study used two treatments, namely P0: Control (commercial feed) and P1: the use of 50% commercial feed and 50% additional feed in the form of tofu waste fermented with probiotics. Parameters observed were growth, feed efficiency, and survival of tilapia. The results showed that the P0 treatment resulted in absolute length and absolute weight growth of 0.76 cm and 0.64 g, respectively, feed efficiency 43.43%, and tilapia survival of 88%, while P1 resulted in absolute length growth and absolute weights were 1.11 cm and 1.3 g, respectively, feed efficiency was 82.12%, and tilapia survival was 84%.